Comparative Analysis of the Development of Acquired Radioresistance in Canine and Human Mammary Cancer Cell Lines - Gray, Mark; Turnbull, Arran K.; Meehan, James; Martínez-Pérez, Carlos; Kay, Charlene; Pang, Lisa Y.; Argyle, David J. (Frontiers in Veterinary Science, 2020)
Research using in vitro canine mammary cancer cell lines and naturally-occurring canine mammary tumours are not only fundamental models used to advance the understanding of cancer in veterinary patients, but are also regarded as excellent translational models of human breast cancer. Radiotherapy is commonly used to treat human breast cancer; however, the tumour’s response to radiation depends not only on its innate radiosensitivity, but also on tumour repopulation by cells that develop radioresistance. Comparative canine and human studies investigating the molecular mechanisms of radioresistance may lead to the development of effective cancer treatments that benefit both species. In this study, we developed a canine mammary cancer (REM-134) radioresistant (RR) cell line and investigated the cellular mechanisms related to the development of acquired radioresistance. We performed a comparative analysis of this resistant model with our previously developed human breast cancer radioresistant cell lines (MCF-7 RR, ZR-751 RR and MDA-MB-231 RR), characterising inherent differences through genetic, molecular and cell biology approaches. RR cells exhibited enhanced migration/invasion, with evidence of epithelial-to-mesenchymal transition. Similarities were identified between the REM-134 RR, MCF-7 RR and ZR-751 RR cell lines in terms of the pattern of expression of both epithelial and mesenchymal genes, in addition to WNT, PI3K and MAPK pathway activation. Following the development of radioresistance, transcriptomic data indicated that the parental MCF-7 and ZR-751 cell lines changed from a luminal A classification to basal/HER2-overexpressing (MCF-7 RR) and normal-like/HER2-overexpressing (ZR-751 RR). These radioresistant subtypes were similar to the REM-134 and REM-134 RR cell lines, which were classified as HER2-overexpressing. To our knowledge, our study is the first to develop a canine mammary cancer RR cell line model and provide a comparative genetic and phenotypic analysis of the mechanisms of acquired radioresistance between canine and human cancer cell lines. We demonstrate that the cellular processes that occur with the development of acquired radioresistance are similar between the human and canine cell lines; our results therefore suggest that the canine model is appropriate to study both human and canine radioresistant mammary cancers, and that treatment strategies used in human medicine may also be applicable to veterinary patients.